Kesehatan sebagai Dasar Pemilihan Pangan Berpotensi Mencegah Stunting: Studi Kualitatif: Health Concerns as the Fundamental Dietary Choices for Potential Stunting Preventions: a Qualitative Study - Soesanti, Inne; Taufiqurrahman, Taufiqurrahman; Intiyati, Ani; Hidayati, Sri (Amerta Nutrition, 2024)
Background: Pasongsongan Village lies in the Regency of Sumenep on the Island of Madura. It is a village bordered on the north by the Java Sea which is abundant of fish majorly consumed by adults. Whereas, children under two years old are scarcely served with fish in their diets.  Objectives: The study aims to observe any factors relevant to mothers’ choices in serving meals for children under two years of age. Methods: This study used a qualitative approach with an ethnographic design. The informants were eleven mothers and grandmothers whose children were under two years old. Data was collected by way of interviews and observations. Subsequent to the data collection, the triangulation was carried out. Data were analyzed using thematic analysis. Results: The results showed that children under two years of age were provided with complementary foods prior to the age of 6 months old. Four children were barely fed with fish due to numerous myths regarding worm infestation in toddlers of below two years old if they consume fish or any types of animal food. Moreover, six children were served with fish and animal food due to health issues. Conclusions: In conclusion, the mothers’ choices for children’s meals under two years of age in this village were highly influenced by cultural and health concerns. The implication of this study was that selecting food for toddlers under two years old should bring up a positive impact on their growth.